Engineered Spider Silk Proteins for Biomimetic Spinning of Fibers with Toughness Equal to Dragline Silks (Adv. Funct. Mater. 23/2022). (3rd June 2022) - Arndt, Tina; Greco, Gabriele; Schmuck, Benjamin; Bunz, Jessica; Shilkova, Olga; Francis, Juanita; Pugno, Nicola M; Jaudzems, Kristaps; Barth, Andreas; Johansson, Jan; Rising, Anna
Abstract : Engineered Spider Silk Protein In article number 2200986, Anna Rising and co‐workers present the impressive strength of spider silk fibers conferred by poly‐alanines in stacked β‐sheets (steric zippers in pink). By protein engineering and expression in prokaryotic hosts, they have done what spiders cannot do: increase the hydrophobicity and intermolecular interactions of the steric zippers (turquoise) thereby generating stronger artificial spider silk.